Pretrial Determination of Suspects in Corruption Cases: A Critical Analysis of Judge Sarpin Rizaldi's Decision and Its Implications for Combating Corruption in Indonesia - Sipayung, Baren; Wahyudi, Andi (PT. Riset Press International, 2024)
The pretrial decision in the BG case (No. 04/Pid.Prap/2015/PN.Jkt.Sel) represents a pivotal moment in Indonesian legal history, significantly impacting the landscape of pretrial mechanisms and the balance of power in law enforcement. This research delves into the implications of this landmark decision, examining its role in expanding the scope of pretrial authority to include the review of suspect designations, a move that has since been codified through amendments to the Criminal Procedure Code. The study further explores the decision's emphasis on upholding the presumption of innocence, a fundamental human right often overlooked in the pursuit of justice. Additionally, the research scrutinizes the decision's impact on the authority of the Corruption Eradication Commission, highlighting the need for a delicate balance between robust law enforcement and the protection of individual rights. By analyzing legal documents, scholarly literature, and the socio-political context surrounding the case, this research provides a comprehensive understanding of the decision's transformative effect on Indonesia's legal system and its broader implications for the fight against corruption.